A first generation BAC-based physical map of the Asian seabass (Lates calcarifer). - Jun Hong Xia (Public Library of Science (PLoS), 2010)
Background The Asian seabass (Lates calcarifer) is an important marine foodfish species in Southeast Asia and Australia. Genetic improvement of this species has been achieved to some extent through selective breeding programs since 1990s. Several genomic tools such as DNA markers, a linkage map, cDNA and BAC libraries have been developed to assist selective breeding. A physical map is still lacking, although it is essential for positional cloning of genes located in quantitative trait loci (QTL) and assembly of whole genome sequences. Methodology/principal findings A genome-wide physical map of the Asian seabass was constructed by restriction fingerprinting of 38,208 BAC clones with SNaPshot HICF FPC technique. A total of 30,454 were assembled into 2,865 contigs. The physical length of the assembled contigs summed up to 665 Mb. Analyses of some contigs using different methods demonstrated the reliability of the assembly. Conclusions/significance The present physical map is the first physical map for Asian seabass. This physical map will facilitate the fine mapping of QTL for economically important traits and the positional cloning of genes located in QTL. It will also be useful for the whole genome sequencing and assembly. Detailed information about BAC-contigs and BAC clones are available upon request.